2014
DOI: 10.1590/1516-4446-2013-1230
|View full text |Cite|
|
Sign up to set email alerts
|

Anxiety disorders are associated with quality of life impairment in patients with insulin-dependent type 2 diabetes: a case-control study

Abstract: Objective: To assess the presence of anxiety disorders and quality of life in patients with insulindependent type 2 diabetes. Methods: Case-control study of 996 patients with type 2 diabetes and 2,145 individuals without diabetes. The sole inclusion criterion for the case group was insulin-dependent type 2 diabetes. We compared the case and control groups for sociodemographic variables, laboratory and clinical data, and presence of anxiety disorders. Quality of life was evaluated using the WHOQOL-BREF instrume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 26 publications
4
18
2
2
Order By: Relevance
“…The determination that patients with DM2 present low HRQoL coincides with previously published results in which DM2 had a negative impact on QoL, mediated by factors such as the need for a strict dietary plan, exercise and a specific treatment regimen [29, 30]. The findings in the literature regarding the QoL of patients with DM2 and its association with sociodemographic factors have been variable.…”
Section: Discussionsupporting
confidence: 82%
“…The determination that patients with DM2 present low HRQoL coincides with previously published results in which DM2 had a negative impact on QoL, mediated by factors such as the need for a strict dietary plan, exercise and a specific treatment regimen [29, 30]. The findings in the literature regarding the QoL of patients with DM2 and its association with sociodemographic factors have been variable.…”
Section: Discussionsupporting
confidence: 82%
“…Type 1 population with diabetes appears since childhood and it possible that increase in glucose and indicated as predictive of high anxiety [18,[23][24][25][26][27][28][29][30]. Also, they must have frequent self-monitoring and reasonable application of injectable insulin by the glucose level may contribute to this higher prevalence of anxiety present in type 1 patients [30,31]. As the results of this study showed, both types require a warning for the treatment of that emotional disturbance [14,15,26,32].…”
Section: Discussionmentioning
confidence: 90%
“…There was a high prevalence in social phobia, panic disorders or agoraphobia, psychological distress, OCD and GAD in type 1 patients with diabetes compared with type 2 [14][15][16]21,31,32]. Type 1 population with diabetes appears since childhood and it possible that increase in glucose and indicated as predictive of high anxiety [18,[23][24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations